Cláusula de não concorrência no contrato de emprego: efeitos do princípio da proporcionalidade - Oliveira Neto, Célio Pereira (2013)
Although there isn‟t a specific rule in the native law, the application of the non concurrence clause profits from the constitutional protection, which is based on the free initiative, private property, free concurrence, property law, consumer defense and general freedom law. Due to constitutional propagation, it enjoys equally of protection in the general clauses of the objective good faith and social function, besides the lawfulness presumption of the contract. On the other hand, there are some directives that can‟t be disregarded when having to limit the freedom right of the work. Indeed, the economical order must be based on the importance of the human work, as well as the reduction of the social inequalities and in the search of the perfect job. Moreover, the private property is established on the basis of the free exercise of any work, occupation or profession, that is to say, it must be observed the social right of the worker in choosing the developed activity, this means that any act that disrespect the importance of the work can be understood as unconstitutional. There is a clear confront between the non concurrence clause and the freedom work both under the constitutional protection in the articles 5° and 170 of the CF. The solution of this conflict is coped with the principles of proportionality, which it justifies and limits the application of the non concurrence clause. However, to reach such point, it‟s necessary the constitutional passage about the traditional methods of constitutional interpretation getting to the pos-positivist moment, taking care of the constitutional‟s principles of interpretation reading as a leading of the whole arrangement, differing from the rules relating them with the principle of proportionality use and its sub-principles of adequacy, necessity and proportionality in the strict way